Implementation of Mikrotik Wireless Backhaul for Internet Provisioning in Baturaja Village to Support Digital Transformation - Alfansa Yusuf; Adi Wibowo (SEAN Institute, 2025)
This study analyzes the implementation of a wireless backhaul network using Mikrotik devices to provide stable internet access for Baturaja Village, Sungkai Utara District, which has not yet been reached by fiber optic infrastructure. The main objective is to develop an alternative network using a point-to-point (PtP) wireless link from the District Office as the internet source to the Village Office as the recipient. The research adopts the Network Development Life Cycle (NDLC), covering initiation, analysis, design, implementation, testing, and monitoring stages. The results show that the PtP backhaul using Mikrotik LHG/SXT successfully provides stable connectivity with average RSSI –52 dBm, CCQ above 90%, latency under 15 ms, and no significant packet loss. This connectivity improves the performance of administrative services, the Village Information System (SID), and supports overall digital transformation efforts. The study concludes that wireless backhaul is an effective, low-cost solution for rural areas lacking fiber optic access